Implementasi Bank Emas di Indonesia: Analisis Hukum Positif dan Tinjauan Syariah (Studi Kasus Bank Syariah Indonesia) - Kurniawan, Rachmad Risqy (Lembaga Yasin AlSys, 2025)
This research is motivated by the inauguration of Bank Emas (Gold Bank), which has become a topic of discussion among the public and raises regulatory and Sharia challenges that require analysis. The objective of this study is to discuss the Implementation of Bank Emas in Indonesia: An Analysis of Positive Law and Sharia Review (Case Study of Bank Syariah Indonesia). This research examines the legal basis, including the P2SK Law and relevant OJK Regulations, and evaluates the products and services of Bank Emas BSI based on the DSN-MUI fatwa and the principles of Islamic muamalah. The research method employed is a literature study and qualitative analysis of statutory regulations, religious edicts (fatwa), and related secondary data, using a normative juridical approach. The research findings indicate that: 1) From a positive law perspective, specific regulations detailing the operations of Bank Emas in Indonesia are stipulated in OJK Regulation Number 17 of 2024, as a derivative of the P2SK Law. 2) From a Sharia perspective, the concept of Bank Emas is considered in line with the principles of fiqh muamalah, provided that it adheres to valid contract stipulations, avoids usury (riba), and maintains fairness in transactions. The case study at BSI shows the potential for implementing the gold bank concept through its existing products, including Digital Gold Savings, Gold Installments, Digital Gold Trading, Gold Pawn, and Gold ATMs, which facilitate public access to gold investment and transactions. These products are in accordance with the positive legal framework, although they may not yet fully comply with Islamic Sharia principles. This research recommends the necessity of synergy between regulatory authorities, fatwa institutions, and Islamic banking to formulate a legal framework and business model for Bank Emas that aligns with both positive law and Sharia principles.